Latinamerican Dividends: do they fit in any theory? (2007)
We test different predictions of the pecking order and trade-of theories for the dividends of a sample of Latin-American firms in seven countries covering the years 1999 to 2005. Most of the theoretical predictions are confirmed by the data; our tests also report a high speed of adjustment in the dividend levels of the firms in the sample. A simple model testing the effect of the payout level on the dividend yield, find some support for the tax advantage of capital gains over dividends